Upaya Peningkatan Kesadaran Masyarakat Terhadap Kebersihan dan Kenyamanan Kampung - Romi Gunawan; Merri Anitasari; Roosemarina A. Rambe (UNIB Press, 2022)
Kebun Keling Village is a village with the opportunity to get a positive effect because administratively it is located in a tourism area which is always visited by every tourist who comes to Bengkulu City. Cleanliness and convenience around the village are important factors to increase the satisfaction of local and non-local tourists. The purpose of this activity is to provide exposure, discussion and setting of slogans to increase public awareness of cleanliness and convenience, especially for the community in Kebun Keling Village, Teluk Segara District, Bengkulu City. The results show that the people of Kebun Keling Village are aware of the cleanliness and convenience of the village environment.